PARTISIPASI MELALUI PENGABDIAN MASYARAKAT DALAM PEMBUATAN TANDA JALAN UNTUK GANG-GANG DI KELURAHAN MEKARSARI KECAMATAN PULO MERAK - Dini Martinda Lestari; Ratu Sifa Ni'mah (Yayasan Education and Social Center, 2023)
Street name signs are an important means of providing information about the location and names of roads in an area. Unfortunately, in Mekarsari Village, Pulo Merak District, there are no street signposts which makes it difficult for outsiders to find locations in the area. However, there is good news, because the Community Service Team of Bina Bangsa University students and lecturers has planned a solution to overcome this problem by making a special street name sign for Mekarsari Village. The method to be used is direct partner settlement. Making street name signs will include 6 units, with a size of 20 x 40 cm and a height of 165 cm. The sign will have a blue color with white writing, consisting of three parts, namely the name of the street, the name of the village, and the logo of the University of Bina Bangsa (Uniba) as a form of the university's active participation in this program. The street name sign will be installed by implanting it with a casting as deep as 20 cm, so that it is sturdy and durable. Installing a street name sign will provide significant benefits to the community, because it will make it easier for them to find a location in Mekarsari Village. This will have a positive impact on mobility, tourism, as well as the safety and comfort of the public and visitors. With clear and informative street name signs, outsiders will no longer have difficulty finding locations in Mekarsari Village. Everyone will feel more assisted and directed, and this will be a real example of how collaboration between universities and the community can have a positive impact on the progress and welfare of the local area